Pengaruh Current Ratio, Cash Ratio, Quick Ratio dan TATO Terhadap Price to Book Value Sub Sektor Farmasi di BEI Periode 2020-2024 - Nida Amalia; Heidi Siddiqa (PT. Alahyan Publisher Sukabumi, 2026)
This study examines the influence of Current Ratio (CR), Cash Ratio (CaR), Quick Ratio (QR), and Total Asset Turnover (TATO) on Price to Book Value (PBV) in pharmaceutical companies listed on the Indonesia Stock Exchange (BEI) from 2020–2024. Employing multiple linear regression on 9 companies (45 data points), results indicate all independent variables positively and significantly affect PBV partially (Sig. <0.05) and simultaneously (F=13.310; Sig.=0.000). The model explains 57.1% of PBV variation (R²=0.571), led by CR (β=0.665). Findings align with signaling theory: strong liquidity and asset efficiency signal positive financial health to investors, boosting post-pandemic pharmaceutical valuations. This research fills gaps in prior conflicting studies, offering managers guidance to optimize liquidity and reduce risks, while aiding investors in assessing stock market potential more accurately.